DOI: 10.18174/560520
|View full text |Cite
|
Sign up to set email alerts
|

The role of tradeoffs among life-history traits in a filamentous fungus

Abstract: Rich resource Mycelium dense and compact for resource exploitation Poor resource Mycelium thin for resource exploration B: Resource durability Short-lived resources (e.g., dung or rotting fruit) Fast mycelial growth for resource capture and then one-time reproduction after resource capture ("bang-bang life-history")semelparous life style Long-lived resources (e.g., dead tree) Slower growth and late reproduction start, with multiple reproductive periods -iteroparous life style C: Presence of competition No inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 197 publications
0
1
0
Order By: Relevance
“…In fungi, they often present with phenotypes of reduced sporulation and flattened growth on agar media Fleißner et al, 2005). Recent work on laboratory evolution in fungi has shown that actually such cheating mutations are commonly encountered in many species Nandimath, 2022). While largely similar to the ascomycete lifecycle, the lifecycle of basidiomycetes, particularly those that produce mushrooms has some notable differences.…”
Section: The Fungal Lifecycle and Vulnerabilities To Cheatingmentioning
confidence: 99%
“…In fungi, they often present with phenotypes of reduced sporulation and flattened growth on agar media Fleißner et al, 2005). Recent work on laboratory evolution in fungi has shown that actually such cheating mutations are commonly encountered in many species Nandimath, 2022). While largely similar to the ascomycete lifecycle, the lifecycle of basidiomycetes, particularly those that produce mushrooms has some notable differences.…”
Section: The Fungal Lifecycle and Vulnerabilities To Cheatingmentioning
confidence: 99%